# Put these in the form y=mx+c?

#### Desagni

Put these in the form y=mx+c as not sure how to do this?

6x-5=2y 4x+2y=7 3y=4x+6 000

3x-7=6y 3x+3y=6 7y+6x=60 000

Many thanks xx

#### skeeter

Math Team
$ax + by = c$

$by = -ax + c$

$y = -\dfrac{a}{b} x + \dfrac{c}{b}$

1 person

#### NinjaX3

Hello Desagni, this was what I found for the 6 equations and turned it into slope formula.
1) 6x-5=2y slope formula is: Y=3x-(5/2)
2) 4x+2y=7 slope formula is: Y=-2x + 7/2
3) 3y=4x+6 slope formula is: Y= (4/3)x +2
4) 3x-7=6y slope formula is: Y= (1/2)x-(7/6)
5) 3x+3y=6 slope formula is: Y= -x+2
6) 7y+6x=60 slope formula is: Y= (-6/7)x + (60/7)

The idea Desagni is rearranging the equation to fit the slope formula which is y=mx+b.
This should help. Let me know if you have any questions.

#### Otis

â€¦ I found for the 6 equations and turned it into slope formula â€¦

â€¦ The idea â€¦ is to fit the slope formula which is y=mx+b â€¦
Hi. Actually, the idea is to solve the given equations for y. That doesn't require using the slope formula.

You're using the wrong name for the form y=mx+b. That's called the Slope-Intercept form because it shows both the slope (m) and the y-intercept (0,b).

Here is the Slope Formula; we use it to calculate the slope when we have coordinates of two points on the line (x1,y1) and (x2,y2).

m = (y2 - y1)/(x2 - x1)

1) 6x-5=2y slope formula is: Y=3x-(5/2)
2) 4x+2y=7 slope formula is: Y=-2x + 7/2
3) 3y=4x+6 slope formula is: Y= (4/3)x +2
4) 3x-7=6y slope formula is: Y= (1/2)x-(7/6)
Here's a couple notes about notation, Ninja. We don't need grouping symbols around some values of b. Technically, it's not wrong to type them, but they don't really do anything, above. However, it is good form to not switch back and forth between using symbols Y and y. Those are different symbols, in math, so pick one or the other and use it consistently. Cheers

2 people

#### Greens

This website is equipped with a $\LaTeX$ translator so that you can use the fancy math typesetting you see in Skeeter's post in this thread. You both may find it useful.

See (http://www.docs.is.ed.ac.uk/skills/documents/3722/3722-2014.pdf) Chapter 6 for the basics.

as an example:

$\displaystyle m = \frac{y_2 - y_1}{x_2 - x_1}$

1 person

#### NinjaX3

Thank you I will fix that and be consistent.